PENGELOLAAN ARSIP SERTIFIKAT HALAL GUNA MEWUJUDKAN SAFETY DAN SECURITY DOCUMENT - Putri, Dewita; Priambodo, Bayu (Jurnal Sosial Humaniora Sigli, 2024)
The purpose of this study is to find out how halal certificate document archives are managed in the field of Production and Business Restructuring at the East Java Province Cooperatives and SMEs Service. This research is a qualitative type of research which uses a descriptive approach as the research method. Observation, interviews, and documentation are used as data collection methods in this research, so that after the research data is obtained, the next process is data analysis using the stages of reducing the data that has been obtained, presenting the data, and drawing conclusions. The subjects of this research are staff from the Production and Business Restructuring (PRU) division of the East Java Department and SMEs who have carried out archive activities at any time. From the results of the research that has been carried out, it shows that the results of the analysis of the four indicators based on Sedarmayanti's (2003) theory, namely management of incoming and outgoing mail, archive storage, archive rediscovery, and archive maintenance, it can be concluded that archive management of certified documents is halal in the field of PRU cannot be said to be optimal enough.Keywords : Archives Management, Halal Certificat,  PRU field